Analisis Penerapan Cost Containment pada Kasus Sectio Caesarea dengan Jaminan BPJS di RS Pemerintah XY di Kota Bogor Tahun 2016 - Nazirah Istianisa, Nazirah Nazirah Istianisa; Oktamianti, Puput (Jurnal Ekonomi Kesehatan Indonesia, 2017)
Prospective payment system with INA-CBG’s fare for cases using BPJS Insurance demands hospital to control their cost. This study aims to see the cost containment in XY Hospital through the implementation of clinical pathway, drug formulary, and incentive structure. The study looked into Sectio Caesarea cases from January to March 2016, using quantitative method, comparing BPJS claim with hospital billing and assesst the implementation of clinical pathway using qualitative method through in depth interview. Result shows there is deficit amount of Rp.1.014.125.684,00 and the average of deficit per case is Rp.4.899.157,89. Eighty four percent of cases have length of stay in accordance with clinical pathway. From those cases, 96% has concordant doctors visit, 21% has concordant drug usage, and 48% has concordant laboratory diagnostic test. The hospital formulary uses the national formulary. It is found that XY Hospital does not have an evaluation system for clinical pathway implementation and drug usage. The incentive structure that is used is fee-for-service system which is not suitable for prospective payment method.